Etude des crustacés de la lagune El Mellah, El-Kala, El-Taref - Messaoudene Hana; Meghezoui Amina (My University, 2018)
The Mellah lagoon is an integral part of El-Kala national park; it is exploited in a traditional way. The economic needs and the ecological context of the lagoon, have valued this unique and limited area.The lagoon communicate with the sea by a long and narrow channel which play a major role in the crustacean’s distribution and abundance. In general, the study of the population structure (density) and biomass of Mellah’s crustaceans during four months (January, February, July, August) and through six stations, showed that the Mellah contains an abundance of up to 2240 ± 99.57ind.m-2 and a low biomass of 7.331 gm-2 in comparison with the majority of other Mediterranean lagoons. Moreover, it should be remembered that the crustaceans register (9) are dominated by three species (Corophium insidiosum , Gammarus aequicauda , Cyathura carinata )spread over two different sectors according to their resistance and their biological need which plays a major role in their monthly distribution. ----------------------------------------------------------------------------------------- تنتمي بحيرة الملا ح الى الحظيرة الوطنية للقالة وهي مستغلة في الصيد وتربية الرخويات بطريقة تقليدية. الاحتياجات الاقتصاديةوالبيئية للبحيرة كجزء لا يتجزأ من الأراضي الرطبة لهذه المنطقة المقيدة والفريدة من نوعها. تتواصل البحيرة مع البحر عبر قناة طويلة وضيقة تلعب دوراً رئيسياً في توزيع ووفرة القشريات. بشكل عام، اظهرتدراسة التركيبة السكانية (الكثافة) والكتلة الحيوية لقشريات الملاح خلال أربعة أشهر (يناير،فبراير،يوليو، أغسطس) من خلال ستة محطات ان الملاح يحتوي وفرة (2240 ± 99.57 كونا -2 م) وكتلة حيوية منخفضة (7.331 غ م -2) مقارنة مع معظم البحيرات المتوسطية. علاوة على ذلك، يجب أن نتذكر أن أعداد القشريات (9) تهيمن عليها ثلاثة أنواع(Corophium insidiosum , Gammarus aequicauda , Cyathura carinata) موزعة على قطاعين مختلفين وفقا لمقاومتها وحاجتها البيولوجية التي تلعب دورا رئيسيا في توزيعها خلال الأشهر. ------------------------------------------------------------------------------------------------ La lagune Mellah est une partie intégrante du Parc National d’El-Kala qui est exploitée de façon traditionnelle. Le besoin économique et le contexte écologique de la lagune en tant que partie intégrante de la zone humide, ont valorisé cette étendue restreinte et unique. La lagune communique avec la mer par un chenal long et étroit qui joue un rôle majeur dans la distribution et l’abondance des crustacés. D’une manière générale, L’étude de la structure démographique (densité) et de la biomasse des crustacés du Mellah au cours de quatre mois (janvier, février, juillet, aout) et à travers six stations, a montré que le Mellah renferme des abondances allant jusqu'à2240 ± 99,57ind.m-2 et des biomasses de 7,331 g.m-2 faibles en comparaison avec la majorité des lagunes méditerranéennes. Par ailleurs, il faut rappeler que les crustacés recenser (9) sont dominer par trois espèces (Corophium insidiosum,Gammarus aequicauda,Cyathura carinata) repartie sur deux diffèrent secteurs selon leur résistances et leur besoin biologique qui joue un rôle majeur dans leur distribution à travers les mois.